Analyzing the Turkish and Arabic Subtitle Translations of English Idioms in the Animated Movie Ice Age: The Meltdown - Arife Eray; Muammer Sarıkaya (Şarkiyat Mecmuası)
Idioms play an important role in cultural formation and are also an indispensable part of a language. These phrases usually have different unique meanings and cause much confusion in the translation process. Idioms carry the semantic values of each society and contain the customs, traditions, and lifestyles of that geography; thus, they may not have a direct equivalent in the target language.Therefore, the translation with the closest meaning to the desired expression in the source language is preferred in the translation process. As with every kind of translation, idioms are frequently observed in audio-visual translation products as well. Just as the importance of audio-visual translations has increased these days in the communications between different societies, so has the interest of translation scholars in this field also increased. This brings up dubbing and subtitle translation studies, which are the two basic types of audio-visual translation. This study analyzes the types of English idioms used in Ice Age: The Meltdown, produced by Blue Sky Studios in 2006 as the second in the series of animated Ice Age movies, and the translation strategies used for the Turkish and Arabic subtitle translations of the idioms encountered in this movie. The data analysis section of this study utilizes Chitra Fernando’s idiom typology, Henrik Gottlieb’s subtitle translation strategies, and Mona Baker’s idiom translation strategies. Within this scope the analyses evaluate whether the idioms in question are source- or target language-oriented. In this context, the study has determined that the analyzed translations are closer to the target language.